Dynamics of population immunity due to the herd effect in the COVID-19 pandemic - Clemente-Suárez, Vicente Javier; Hormeño-Holgado, Alberto; Jiménez, Manuel; Benitez-Agudelo, Juan Camilo; Navarro-Jiménez, Eduardo; Perez-Palencia, Natalia; Maestre-Serrano, Ronald; Laborde-Cárdenas, Carmen Cecilia; Tornero-Aguilera, José Francisco (Vaccines, 2020)
The novel Coronavirus 2 Severe Acute Respiratory Syndrome (SARS-Cov-2) has led to the Coronavirus Disease 2019 (COVID-19) pandemic, which has surprised health authorities around the world, quickly producing a global health crisis. Different actions to cope with this situation are being developed, including confinement, different treatments to improve symptoms, and the creation of the first vaccines. In epidemiology, herd immunity is presented as an area that could also solve this new global threat. In this review, we present the basis of herd immunology, the dynamics of infection transmission that induces specific immunity, and how the application of immunoepidemiology and herd immunology could be used to control the actual COVID-19 pandemic, along with a discussion of its effectiveness, limitations, and applications.
Keywords: SARS-Cov-2; COVID-19; herd immunology; vaccines; pandemic; epidemiology; Scopus; JCR